The function of gallant texts as models of and models for gallant Conduite around 1700 (KULT_online, 2014)
The literary and historical study Conduite und Text by German philologist Dirk Rose is the first extensive monograph about gallant author Christian Friedrich Hunold alias Menantes (1680‒1721). The study delivers insight into the wide and contradictory oeuvre of Hunold, and gives a theoretical approach for reconstructing the relevance and impact of a socio-cultural model of gallant interactions and communications (galante conduite). According to Rose, the interdependency of text and conduite implies the “Produktion einer spezifischen Differenz” that affects gallant text production which is then also, on the other hand, the condition for developing a model of gallant conduit. Text and conduite cause each other in “spezifischer Differenz”. Gallant texts receive a function of model and for modelling that Rose attempts to explain.